Mutual adaptations between hosts and parasites determine stress levels in eels. (April 2021) - Honka, K.I.; Sures, B.
Abstract: Invasive parasites may severely affect their new hosts. Two invasive parasites occurring in the European eel ( Anguilla anguilla ) are the Asian swim bladder nematode Anguillicola crassus and the Ponto-caspian acanthocephalan Pomphorhynchus sp., which were introduced to the river Rhine in the early 1980/90s. The Japanese eel ( Anguilla japonica ), as the native host of A. crassus, developed mutual adaptations to the swim bladder parasite, which are lacking in the European eel. Therefore, after its spread to Europe, infestations of European eels with A. crassus were found to be more severe and caused massive swim bladder wall damages mainly due to the feeding activity of the adult nematodes. A suppression of the immune system also appears to be likely, which allows secondary infections e.g. by bacteria or other parasites in European eels. Acanthocephalans of the genus Pomphorhynchus have not been described so far in Japanese eels, in contrast to European eels, which regularly show infestations with Pomphorhynchus sp. By using these differentially adapted host-parasite associations for experimental studies, host stress responses were examined in the present study in relation to the degree of mutual adaptations between eel hosts and parasites. Under laboratory conditions, Japanese and European eels were each inoculated with A. crassus and Pomphorhynchus sp., respectively, to investigate their stress responses against differently adapted parasites. The stress response was determined by analyzing plasma levels of cortisol, which is the main corticosteroid hormone during stress response of fish. The results show a strong cortisol release in European eels after infestation with A. crassus whereas Japanese eels only react against Pomphorhynchus sp. infestations. These results are consistent with the initial hypothesis that a low degree of host-parasite adaptations lead to stronger host stress responses against the parasite. Graphical abstract: Image 1 Highlights: We measured cortisol as the main corticosteroid hormone in fish. Japanese and European eels were inoculated with A. crassus and Pomphorhynchus sp. Lower mutual adaptations lead to a higher stress response in host-parasite-systems.